Strategi Pemerintah Kota Surabaya dalam Menghadapi Kenaikan Harga Beras - Zahroh, Putri Amalia; Lukman Arif; Annisa Nur Firdaus; Nayani Alya Aquila Muzdalifah; Ivan Prasetyo Nugroho (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The phenomenon of rising rice prices often occurs due to several influencing factors, one of which comes from the climate and the existence of a bumper harvest. In addition, higher market demand than production is also one of the causes. Surabaya as a city that is predicated as a consumer rather than a producer of rice is very careful in maintaining the existing rice supply. Public panic over the increase in rice prices has led the government to issue programs as a strategy to overcome it, one of which is consistently implemented to date is the Cheap Market Movement. The purpose of this research is to describe the government's strategy in overcoming the price of rice based on the five indicators of Geoff Mulgan's theory. This research uses descriptive qualitative research methods by taking results from interviews as primary data and secondary data obtained from literature reviews such as articles, journals, and relevant references. The results of this study reveal that the Cheap Market Movement program and the existence of SPHP rice can help people's lives and achieve the success rate of strategies issued by the Surabaya city government, especially by the Food Security and Agriculture Office.